The Efficacy of On-Site Integration Screening and Microelimination Programs for Chronic Hepatitis C in a Detection Center: A Comparison of the Treatment Outcomes and Characteristics of Incarcerated Patients and Outpatients - Hsuan-Yuan Chang; Su-Hung Wang; Hsing-Tao Kuo; Ming-Jen Sheu; I-Che Feng; Chung-Han Ho; Jui-Yi Chen; Chi-Shu Sun; Chi-Hsing Chen; Cheng-Yi Lin; Chun-Chi Yang (International Journal of Hepatology)
We aimed to analyze the different patient characteristics and treatment outcomes (such as sustained viral response, SVR) between incarcerated patients with chronic hepatitis C (CHC) and those with CHC from the outpatient department through an on-site integrated screening and microelimination program in a detection center. In this retrospective study, which ran from May 2021 to April 2022, we included 32 consenting male prisoners aged at least 20 years who were willing to participate in the study. Members of the control group (who received DAAs in an outpatient setting) were selected from the treated CHC patient databank of individuals who received DAA regimens at Chi Mei Hospital between January 2021 and December 2022. The patients in the two groups did not differ significantly in terms of age, FIB-4 score, HCV RNA, HBV coinfection, hemogram findings, coagulation profiles, and renal function tests. However, the patients in the incarcerated group had a significantly different genotype distribution compared to the control group, significantly lower liver enzyme levels, and higher albumin and bilirubin levels compared to those in the control group. The rate of SVR to DAA treatment obtained among incarcerated patients did not differ significantly from that obtained among patients in the control group. Loss to follow-up (for several reasons) is a major reason for treatment discontinuation among these patients.